2011
DOI: 10.1111/j.1399-0012.2011.01516.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of stable PGI2analog iloprost on early graft viability after liver transplantation: a pilot study

Abstract: We suggest iloprost to be beneficial for early post-transplant liver function. If the rate of PDF can be significantly reduced with this treatment concept, it should be analyzed in a larger number of patients (ISRCTN95672167).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 51 publications
(53 reference statements)
2
26
0
2
Order By: Relevance
“…Complete inclusion and exclusion criteria are displayed in Table 1. According to the experience from the pilot study [14] about 83% of primarily enrolled patients reached respiratory and circulatory stable conditions after LT as precondition for trial medication. To randomize 356 patients after LT written informed consent has to be obtained from about 430 patients fulfilling the study criteria observable before LT.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Complete inclusion and exclusion criteria are displayed in Table 1. According to the experience from the pilot study [14] about 83% of primarily enrolled patients reached respiratory and circulatory stable conditions after LT as precondition for trial medication. To randomize 356 patients after LT written informed consent has to be obtained from about 430 patients fulfilling the study criteria observable before LT.…”
Section: Methodsmentioning
confidence: 99%
“…From 2006 to 2008, we evaluated the impact of the PGI 2 analogue iloprost in 80 liver transplanted patients in a prospective, randomized (1:1), open-label, single-center pilot study [14]. Our data indicate that intravenous administered PGI 2 analogue iloprost (1 ng/kg BW/min) improves the graft function, particularly in the early postoperative period.…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has also been shown that this molecule has important roles in immune regulation (Boswell et al, 2011) and some studies suggest that treatment with PGI 2 analogs may improve early graft viability in liver transplant patients, partly by reducing levels of inflammatory cytokines (Barthel et al, 2012). …”
Section: Biosynthesis Of and Signaling By Eicosanoids In T Lymphocytesmentioning
confidence: 99%
“…According to previous clinical experience, doses of 0.5 to 4 ng/kg BW/minute were used for continuous infusion after liver transplant 4,9 and acute limb ischemia. 10 Because the positive effects achieved with 1 ng/kg BW/min were mild, 4 and we knew from clinical experience that a dosage of 4 ng/kg BW/minute usually was difficult to achieve because of adverse events, 9 we used 2 ng/kg BW/minute.…”
Section: Study Design and Dosementioning
confidence: 99%
“…[1][2][3][4] However, although beneficial clinically and experimentally, its use in donor pretreatment is uncommon and the exact recommendations about type of application are pending. [5][6][7] The purpose of this study was to compare 4 different iloprost treatment regimens to a control group and to determine their effect on liver injury and function after extended cold ischemia time (CIT) (20 h) in an isolated 8-hour extracorporeal pig liver perfusion model.…”
Section: Introductionmentioning
confidence: 99%